Oxidative cyclisation and methylene insertion in 1,3-indandione derivatives .The mechanistic studies - Zargar, N .D . (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Dimethyl sulphoxide activated by acetic-anhydride introduces methylthiomethyl group into phenols,oxidises certain medicinally useful secondary alcohols to their corresponding ketones and brings about oxidative rearrangements in different substrates.It converts 4-hydroxy coumarins and dicoumarols,under varying conditions,to a variety of products of both pharmaceutical and mechanistic interest. When1,3-indandione (1) was interacted with this versatile reagent at water bath temperature,it afforded an ylide (2) and an oxidative cyclisation product (3).However,its interaction with Ar –CH = (CN)R,leads to the formation of a mechanistically interesting compound,indeno[1,2-b]-4H pyran(4). DMSO alone has been used as a reagent and yields a number of products of mechanistic interest with different substrates.When 1,3-indandione (1) was refluxed with DMSO alone at elevated temperature,it results the formation of poly(methylene-bis) 1,3-indandione(5) involving methylene group insertion between different 1,3-indandione moieties.Methylene insertion has also been observed when 1,3-indandione (1) was condensed with formaldehyde in presence of alkali carbonates or primary amines to yield (6)and(7) respectively.